Catch Per Unit Effort (CPUE) Dynamic of Scad (Decapterus spp) related to Water Parameters in the Banda Sea - Fajar Indah Ningsih; Am Azbas Taurusman; Budy Wiryawan; Prihatin Ika Wahyuningrum (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The lack of data and information concerning the scad fishing grounds in that area restricts the efficiency of fish capture. This research aims to estimate the CPUE of the scad, map the spatial-temporal dynamics of sea surface temperature (SST) and chlorophyll a (Chl-a), and evaluate the SST and Chl-a relationship to scad catch rates in the Banda Sea. The SST and chl-a were obtained from Aqua MODIS satellite imagery over three years (2020-2022), while scad catch data were obtained from the Kendari Fishing Port. Bivariate correlation analysis was used to assess the relationship between SST, Chl-a, and scad catch rates. The results show a fluctuation trend in CPUE (2020-2022), with CPUE values ranging from 53.41 to 354.65kg/trip. The temporal distribution of SST values ranged from 26.91 to 29.42°C, while the Chl-a concentration ranged from 0.20 to 4.8mg/m³. Spatially, it was higher near the shore and lower offshore. A moderate negative correlation (r = -0.464) was observed between Chl-a and CPUE, while SST showed a weak positive correlation (r = 0.101) with the CPUE. This study recommends integrating field data and satellite imagery to accurately estimate the fishing grounds to improve efficiency and sustainable fisheries management in the Banda Sea.